Improving Students’ Understanding About Materials of Learning Management System Through Project Based Learning - Handayani, Sri; Hakim, Luqman Al; Saptaningsih, Ina (Indonesian Research Journal on Education, 2024)
This research aimed to improve in service training student’s competence in comprehending learning material by applying Project Based Learning (PjBL). This research was a classroom action research which conducted in two cycles. In each cycle there were planning, implementing, observing and reflecting. The subject of the research were 66 students of in service training of PPG FKIP Unisri. Questionaire, observation and interview were employed to collect both qualitative, that there was then being analyzed using constant comparative methods. Based on the data analysis, it can be found that there was significance improvement in applying PjBL to overcome lower competence in understanding learning materials that most of the students understand micro and macro reading skills that comprises words, special terms, sentences, paragraphs, and content in a text. It can be concluded that employing micro and macro reading skills help students to achieve good understanding in reading reading comprehension.